(untitled) (Contemporary Mathematics, 2023)
The study of flow and heat transfer of biomagnetic fluid past a stretching sheet has a significant importance in a number of bio-medical and engineering applications including cancer treatment, drug delivery, magnetic resonance imaging, reducing blood flow during surgeries etc. Owing to these applications, the aim of the present paper is to study an electrically non-conducting Newtonian biomagnetic fluid in the presence of a magnetic dipole over an extendable sheet subject to velocity slip. The governing steady boundary layer equations with the help of similarity transformations were converted into a set of highly non-linear ordinary differential equations which are then computationally solved by applying the bvp4c function technique in MATLAB software. The results show that blood velocity and temperature can remarkably be influenced by the variation of ferromagnetic parameter. As the ferromagnetic parameter increases, the rate of heat transfer of blood is increased while coefficient of skin friction is reduced. We hope that this study could be useful in cancer treatment as well as in drug administration.